Efek Antidiabetes dan Identifikasi Senyawa Dominan Fraksi Kloroform Herba Ciplukan (Physalis angulata L.) - Sediarso, Sediarso; Sunaryo, Hadi; Amalia, Nurul (Majalah Ilmu Kefarmasian, 2012)
Antidiabetic activity of ciplukan (Physalis angulata L.) herb has been widely observed, as an extracts and infusions, proven to reduce blood sugar levels in rats or mice induced by alloxan. The research objective was to evaluate the antidiabetic effect and identify the content of the chloroform fraction ciplukan herb eluated with methanol-ammonia. Antidiabetic effects testing conducted using 30 male white mice (Mus musculus) ddY strain were divided into 6 groups, each consisting of 5 mice. K-1 is a negative control induced by alloxan, K-2, K-3 and K-4 induced by alloxan and treated with the test substance dose of 50 mg/kg bw/day, 100 mg/ kg bw/day, 200 mg/kg bw/day, K-5 is a positive control, induced by alloxan and treated with metformin dose of 65 mg/kg bw, K-6 as normal controls . Each mouse blood samples taken on day 7 and day 14, to test their blood sugar levels. Data were analyzed using one-way anova and multiple differences test. Identification of the content of the chloroform fraction eluated with methanol-ammonia, carried out by gas chromatography mass spectrometry (GC-MS). The results showed that all three doses showed a decrease in blood sugar levels significantly at day 7 , but the decline has not reach normal levels. Blood sugar levels drop significantly and the decline has reached normal occurred on day 14. Dominant content of the chloroform fraction eluated with methanol-ammonia is a class of unsaturated fatty acid chain length is Hexanoic acid, C16H1202, hexadecanoic acid methyl ester, C17H3402, 9-octadecenoic acid methyl ester, C19H3602, Oleic acid butyl ester, C22H4202, 9-octadecenoic acid, C19H3602, Octadecanoic acid, C18H3602, 1,2-Benzendicarboxylic acid, C8H604, and Aplysterylacetate, C31H5202. Another result is that Nordextromethorphan alkaloid compound, Cl 7H23NO. The conclusion is chloroform fraction of ciplukan herb has antidiabetic effects and has a class of compounds content of unsaturated fatty acids, Aplysterylacetate and alkaloid Nordextromethorphan.